How the teacher development ecosystem influences career success: the chain mediation role of school climate and job crafting - Xu, You; Chang, Biru; Guo, Qiuxia (Frontiers in Psychology, 2025)
BackgroundTeachers' career success is increasingly recognized as a multidimensional outcome shaped by individual and contextual factors. Drawing on ecological systems theory and conservation of resources theory, this study investigated how the teacher development ecosystem influences teachers' career success, focusing on the mediating roles of school climate and job crafting.MethodsThe stratified random sampling was used to survey one thousand seven hundred and fifty five teachers across four provinces in China with self-reporting. All participants completed the Teacher Development Ecosystem Questionnaire, the School Climate Questionnaire, the Job Crafting Questionnaire, and the Teacher Career Success Questionnaire. Structural equation modeling was applied to examine the hypothesized relationships and mediating effects.ResultsThe results demonstrated that the teacher development ecosystem significantly and positively predicted teachers' career success. School climate partially mediated this relationship, and job crafting also acted as a mediator. Moreover, school climate and job crafting jointly exerted a chain mediation effect, indicating that a positive school climate promotes teachers' job crafting behaviors, which subsequently enhance their career success. Notably, the findings suggested that job crafting is necessarily mediated by school climate within the chained mediation model.ConclusionThis study extended the application of ecological systems theory to teachers' career development by uncovering the mechanism through which the teacher development ecosystem contributes to career success. The results provide practical implications for fostering supportive school climates and encouraging job crafting behaviors as strategies to enhance teachers' career outcomes.